ANALISIS PENILAIAN KINERJA KEUANGAN PT BANK CENTRAL ASIA Tbk PERIODE TAHUN 2016 – 2020 - Sabri Nurdin; Makmur Marzuki (Jurnal Eksis, 2021)
This research was conducted with the aim of knowing the development of the financial performance of PT Bank Central Asia Tbk for five consecutive years, namely from 2016 to 2020. This type of research is quantitative, namely the source of data used is from external sources and is secondary data derived from of summary financial statements. The data analysis technique used is the ratio analysis technique with the horizontal method, namely by comparing the financial statements of several periods so that the development of the bank's financial performance will be seen.Based on the ratio analysis that has been done, namely the capital ratio, liquidity ratio, and profitability ratio, the results show that. Where the performance capital ratio is good (healthy) because the resulting value exceeds the minimum stipulation for a healthy bank, which is a minimum of 8%. For the liquidity ratio, the development performance finacial is also good (healthy), that is, it does not exceed the provisions set by Bank Indonesia, which is smaller than 110%, and for the profitability ratio for the development of good performance (healthy) because the resulting ROA value exceeds the standard set by Bank Indonesia, namely 1, 5% and the resulting BOPO is also below 93.5% as stipulated by Bank Indonesia. Key woods : the financial performance, the capital ratio, liquidity ratio, and profitability ratio.